AHLI WARIS PENGGANTI DALAM KOMPILASI HUKUM ISLAM - Muhammad Mustofa (UIN Siber Syekh Nurjati Cirebon, 2017)
Kompilasi Hukum Islam (KHI) considered an injustice which felt by the grandchildrenÂ from the daughters according to jumhur, who did not take a part because of the zawi al-arham status, or grandchildren from the sons who are covered by the son, referring to the provisions of KHI which tried to positioned the grandchildren who are covered so grandchildren entitled to acquire heritage treasures as a form of the offer for the concept of justice and welfare for the grandchild who is called the heirs of substitute. The formulation of the problem that wants to find out the answers the are: How is the replacement of the heirs in Kompilasi Hukum Islam? Why does the Kompilasi Hukum Islam determine the heirs of substitute?. To answering the problems above, the writer used law research with the normative juridical approach method, that is a law research conducted by prioritizing the existence of referenced materials or document which called secondary data, includes of primary, secondary, and tertiary law materials. The research specification is an analytical descriptive, which aims to provide an overview of the qualitative methods of law theories and law doctrines as well as the opinions of Islamic jurists.Keywords: The Heirs of Substitute, Kompilasi Hukum Islam (KHI).",